SOUTH KOREA'S HALAL FOOD GASTRO-DIPLOMACY TOWARDS MUSLIM TOURISTS 2009-2022 (CASE STUDY: MUSLIM TOURISTS IN SOUTH KOREA) - Amelia Puspa Tamara; Ajeng Puspa Marlinda (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
South Korea is a country on the southern part of the Korean peninsula and the majority religion is not Islam. To worship or find halal food that is permissible for consumption by Muslims there is quite difficult. After the success of its cultural diplomacy in the form of Hallyu, in 2009 Korea also launched kimchi diplomacy and was quite successful, so that Muslim countries are getting to know Korean cuisine. Then, around 2014 Korea also developed halal food gastro diplomacy for Muslim tourists who traveled to South Korea. There are reasons that make Korea interested in building halal food diplomacy even though the majority of the population is non-Muslim. For this reason, through this paper the author has a research objective to analyze the factors that influence South Korea to develop halal food gastro diplomacy towards Muslim tourists. By using qualitative methods, this study found that South Korea developed halal food gastro diplomacy towards Muslim tourists to build good relations with Muslim countries, and improve the South Korean economy through tourism.